Nations under God : how churches use moral authority to influence policy - Grzymała-Busse, Anna Maria, 1970- (Book collections on Project MUSE., 2015)
"In some religious countries, churches have drafted constitutions, restricted abortion, and controlled education. In others, church influence on public policy is far weaker. Why? Nations under God argues that where religious and national identities have historically fused, churches gain enormous moral authority--and covert institutional access. These powerful churches then shape policy in backrooms and secret meetings instead of through open democratic channels such as political parties or the ballot box. Through an in-depth historical analysis of six Christian democracies that share similar religious profiles yet differ in their policy outcomes--Ireland and Italy, Poland and Croatia, and the United States and Canada--Anna Grzymała-Busse examines how churches influenced education, abortion, divorce, stem cell research, and same-sex marriage. She argues that churches gain the greatest political advantage when they appear to be above politics. Because institutional access is covert, they retain their moral authority and their reputation as defenders of the national interest and the common good. Nations under God shows how powerful church officials in Ireland, Canada, and Poland have directly written legislation, vetoed policies, and vetted high-ranking officials. It demonstrates that religiosity itself is not enough for churches to influence politics--churches in Italy and Croatia, for example, are not as influential as we might think--and that churches allied to political parties, such as in the United States, have less influence than their notoriety suggests"--